10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Wastewater surveillance has been widely adopted since the COVID-19 pandemic, but non-sewered (e.g., onsite) sanitation is a common form of sanitation in cities of low- and middle-income countries. Environmental surveillance in these settings requires alternatives to wastewater. We collected 81 soil samples adjacent to public waste bins inside the sewered and non-sewered areas of Maputo and a 150-meter-wide buffer zone between the two areas, as well as from subsistence farms near the wastewater treatment plant for comparison. We cultured Escherichia coli (E. coli) and determined the prevalence of 29 unique enteric pathogens via RT-qPCR. E. coli concentrations were significantly higher (p < .001) in soils adjacent to public waste bins (mean = 5.1x105 per gram) compared to soils from farms (mean = 8.7x101 per gram). The mean number of unique pathogens was higher in soils from the non-sewered area (mean = 7.9, n = 32 samples) and the 150-meter buffer area (mean = 11, n = 10) compared to the sewered area (mean = 4.6, n = 20) and soils from farms (mean = 3.8, n = 19). Findings demonstrate that the presence of enteric pathogens in soils adjacent to public waste bins were associated with neighborhood sanitation infrastructure. In high-burden settings with poor sanitation, direct examination of soils and other environmental matrices are potentially scalable means of environmental pathogen surveillance to consider beyond conventional matrices.